Outcome of subsequent pregnancies post uterine rupture in previous delivery: A case series, a review, and recommendations for appropriate management. Issue 1 (2nd October 2022) - Dabi, Yohann; Bouaziz, Jerome; Burke, Yechiel; Nicolas‐Boluda, Alba; Cordier, Anne‐Gael; Chayo, Jennifer; Cohen, Shlomo B.
Abstract: Objectives: To provide clinicians with concrete solutions on the best management of and counseling for patients in a subsequent pregnancy following uterine rupture. Methods: A retrospective analysis of patients treated between 2005 and 2020 at Sheba Medical Center was conducted. All patients who had undergone a complete uterine rupture and subsequently had a full‐term pregnancy were included. A literature review was conducted using Pubmed database and including previously published literature reviews. Results: Fifteen patients with subsequent pregnancies following uterine rupture were included in our cohort. Mean interval between rupture and subsequent pregnancy was 3.8 years (range 2.2–6.9 years). One patient had repeat uterine rupture of less than 2 cm at 36 +5 weeksof pregnancy. A total of 17 studies were selected in this literature review, including a total of 774 pregnancies in 635 patients. The risk of repeated uterine rupture was 8.0% (62/774), ranging from 0% to 37.5%. Overall, the risk of maternal death was of 0.6% (4/635), with only four cases reported in three studies. Conclusion: The risk of recurrence after uterine rupture is significant but should not prevent patients from conceiving. Synopsis: This case series and review contributed to define a practical strategy in aiding clinicians to deal with this delicate and rare setting.